2018
DOI: 10.2298/tsci161221202a
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of micro pin-fin heat sink with staggered arrangement

Abstract: The effect of the pin-fin shapes on the overall performance of the carbon nanotube bundles as porous micro pin-fins with in-line and staggered arrangement for the heat transfer and pressure drop is studied using FLUENT 15.0. The results of the study revealed that at 100 < Re < 2000, triangle has the best performance followed by square, rectangle, hexagon and circle in 1 mm height, 15 mm width, and 45 mm length silicon rectangular mini-channel. The staggered configuration gave better heat transfer performance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The nanofluids have also been used to enhance the heat transfer rate by increasing the thermal conductivities of the base fluid using suspended nanoparticles. Arjun and Kumar [11] performed numerical study to optimize the pin fin heat sink using water and CNT. Kumar et al [12] reviewed progression in theoretical modelling of the nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…The nanofluids have also been used to enhance the heat transfer rate by increasing the thermal conductivities of the base fluid using suspended nanoparticles. Arjun and Kumar [11] performed numerical study to optimize the pin fin heat sink using water and CNT. Kumar et al [12] reviewed progression in theoretical modelling of the nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Two correlations were established considering the clearance. To study the effect of the pin shape, Tullius et al [35] and Arjun et al [36] studied the heat transfer characteristics of pin-fin arrays with various pin shapes via numerical simulation. The conclusions revealed the significant effect of pin shape on heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Packing configurations are common elements which are widely used in real applications such as chemical packed bed reactor [1], chromatographic separation [2], and heat sinks [3]. Yang et al [1] revealed that structured packed beds have different flow and heat transfer characteristics compared with randomly packed beds.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [2] found different packing structures such as simple cubic packing, body-centered cubic packing, and face-centered cubic packing may lead to various flow patterns and mass transfer performances in chromatography separation. The pressure drop and cooling performance of heat sinks with different shaped pin-fin structures arranged in staggered and in-line order were studied by Arjun and Kumar [3]. Sayehvand et al [4] studied the forced convective heat transfer over three cylinders in staggered arrangement.…”
Section: Introductionmentioning
confidence: 99%